Herediter spastik parapleji hastalarında tekrarlayıcı transkraniyal manyetik stimülasyon uygulaması - (:unkn) unknown (My University, 2011)
Herediter spastik parapleji (HSP) alt ekstremitelerde ilerleyici spastisite ile karakterize, heterojen bir genetik hastalıktır. Bu hastalarda, spastisite uzun dönem özürlülüğün en önemli nedenidir ve hastaların yaşam kalitelerini önemli ölçüde etkilemektedir. Tekrarlayıcı transkranial manyetik stimülasyon (rTMS) birçok nörolojik ve psikiyatrik hastalığın tanı ve tedavisinde yaygın olarak kullanılmaktadır. rTMS uygulamasının spastisite üzerine olumlu etkileri bildirilmesine rağmen HSP hastalarında yapılmış bir çalışmaya rastlanmadı. Bu yazıda düşük doz rTMS [1 Hz frekansta 20 dakika (1200 atım) süre ile 10 tedavi seansı] tedavisi alan iki HSP hastası sunduk.

Hereditary spastic paraplegia (HSPP) is a heterogeneous genetic disease characterized by progressive spasticity of lower extremities. Spasticity is a major cause of long-term disability in HSPP and significantly affects the functional life of patients. Repetitive transcranial magnetic stimulation (rTMS) is widely used in diagnosis and treatment of many neurological and psychiatric diseases. Although the positive impacts of rTMS for spasticity have been reported, no study has been found on HSPP. We present two HSPP patients treated with low frequency rTMS (20 minutes at a frequency of 1 Hz (1200 pulses), for a period of 10 treatment sessions).
Repetitive transcranial magnetic stimulation in patients with hereditary spastic paraplegia
Keywords: Nörolojik Bilimler